Exploring the Use of Oral Corrective Feedback in Turkish EFL Classrooms: A Case Study at a State University - Özlem Fakazlı (OpenAlex, 2018)
Esta investigación basada en el aula investigó cómo un profesor no nativo de inglés proporcionó comentarios correctivos a los estudiantes de EFL de turco. Más específicamente, el estudio tuvo como objetivo identificar los errores de lenguaje producidos por los estudiantes, los tipos de retroalimentación correctiva empleados por el maestro y la tasa de aceptación de los estudiantes después de la retroalimentación proporcionada. Los datos se recopilaron a través de la grabación de audio, se transcribieron y analizaron en detalle para determinar el tipo de errores de los alumnos, el tipo de comentarios de los maestros y la tasa de aceptación de los alumnos. Los resultados revelaron que se encontró que los errores gramaticales eran el tipo de error más producido, y que los errores léxicos eran el tipo de error menos producido. El estudio también indicó que la refundición fue la preferida con mayor frecuencia, y la solicitud de aclaración fue el tipo de retroalimentación correctiva menos preferida por el docente. También se descubrió que todos los tipos de comentarios condujeron a la corrección exitosa de las expresiones erróneas de los alumnos con una tasa de captación del 100%.

Cette recherche en classe a examiné comment un professeur d'anglais non natif a fourni des commentaires correctifs aux apprenants turcs de l'EFL. Plus précisément, l'étude visait à identifier les erreurs de langue produites par les élèves, les types de rétroaction corrective employés par l'enseignant et le taux de participation des élèves à la suite de la rétroaction fournie. Les données ont été recueillies par enregistrement audio, transcrites et analysées en détail pour le type d'erreurs de l'apprenant, le type de rétroaction de l'enseignant et le taux de participation de l'apprenant. Les résultats ont révélé que les erreurs grammaticales étaient le type d'erreur le plus produit et que les erreurs lexicales étaient le type d'erreur le moins produit. L'étude a également indiqué que la refonte était le type de rétroaction corrective le plus fréquemment préféré, et que la demande de clarification était le type de rétroaction corrective le moins fréquemment préféré par l'enseignant. Il a également été constaté que tous les types de rétroaction ont permis de corriger avec succès les énoncés erronés des élèves avec un taux de participation de 100 % des apprenants.

This classroom-based research investigated how a non-native teacher of English provided corrective feedback to Turkish EFL learners. More specifically, the study aimed to identify language errors produced by the students, corrective feedback types employed by the teacher, and students' uptake rate following the provided feedback. The data were collected through audio-recording, transcribed, and analyzed in detail for the type of learner errors, type of teacher feedback, and rate of learner uptake. The results revealed that grammatical errors were found to be the most produced error type, and lexical errors were found to be least produced error type. The study also indicated that recast was the most frequently preferred, and clarification request was the least frequently preferred corrective feedback type by the teacher. It was also found that all feedback types led to successful correction of erroneous utterances of the students with 100% learner uptake rate.

بحث هذا البحث القائم على الفصل الدراسي في كيفية قيام مدرس اللغة الإنجليزية غير الناطق بها بتقديم ملاحظات تصحيحية لمتعلمي اللغة الإنجليزية كلغة أجنبية الأتراك. وبشكل أكثر تحديدًا، هدفت الدراسة إلى تحديد الأخطاء اللغوية التي ينتجها الطلاب، وأنواع التعليقات التصحيحية التي يستخدمها المعلم، ومعدل استيعاب الطلاب بعد التعليقات المقدمة. تم جمع البيانات من خلال التسجيل الصوتي ونسخها وتحليلها بالتفصيل لنوع أخطاء المتعلم ونوع ملاحظات المعلم ومعدل استيعاب المتعلم. كشفت النتائج أنه تم العثور على الأخطاء النحوية لتكون أكثر أنواع الأخطاء إنتاجًا، وتم العثور على الأخطاء المعجمية لتكون أقل أنواع الأخطاء إنتاجًا. كما أشارت الدراسة إلى أن إعادة الصياغة كانت الأكثر تفضيلاً، وكان طلب التوضيح هو نوع الملاحظات التصحيحية الأقل تفضيلاً من قبل المعلم. كما وجد أن جميع أنواع التعليقات أدت إلى تصحيح ناجح للألفاظ الخاطئة للطلاب بمعدل استيعاب 100 ٪ للمتعلم.
Keywords: Literature and Literary Theory; Corrective feedback; Turkish; Social Sciences; Corrective Feedback; Word error rate; Speech recognition; Language and Linguistics; Vocabulary Acquisition in Second Language Learning; Developmental and Educational Psychology; Psychology; English-Medium Instruction in Higher Education; Language Teaching; Linguistics; Computer science; Mathematics education; FOS: Philosophy, ethics and religion; FOS: Psychology; Philosophy; Incidental Learning; Language Teaching and Second Language Acquisition; FOS: Languages and literature; Arts and Humanities; 10. No inequality; 4. Education; 1. No poverty